The Effect of Fundamentalist Connotations Verbal on the Multiplicity of Interpretive Opinions - Jabir, Muhammad; Ali, Qasim (Islamic Sciences Journal, 2023)
This research marked (the effect of fundamentalist verbal connotations on the multiplicity of interpretative opinions) is an applied rooting study in which the researcher demonstrated the definition of semantics its topics and its impact on the interpreter, in the interpretation and clarification of the meanings of the Noble Qur’an, through an applied study in the interpretation of Qur’anic texts. The researcher focused in his study on the semantic aspect of the fundamentalist and highlighting it as a science that has a great role in explaining the Qur’anic meanings, This study came to confirm the basic role of the science of origins, especially with regard to the investigations of fundamentalist semantics in interpretation through two aspects of this study, which are the theoretical and authenticating side, through the statement and the definition of the fundamentalist semantics contained in this study and its effect on interpretation, by referring to its indications from the fundamentalist and exegetical sources, The other side is the application side, which is represented by highlighting examples from the Qur’anic verses and their interpretation through fundamentalist rules and the semantic effect on the multiplicity of sayings